The accentuation of the Baltic preterit (and of the Balto-Slavic ā-aorist) - Villanueva Svensson, Miguel (Baltistica, 2023)
The Proto-Baltic ē-preterit to ia-presents was normally accented on the root, as expected from a Balto-Slavic perspective and as borne out by close consideration of Baltic circumflex metatony and related issues. Mobile ē-preterits were stressed on the suffix in mobile paradigms: Bl. *arē̍ ‘ploughed’ (Lith. ãrė). In its turn Bl. *arē̍ goes back to early Bl. *arii̯ā̍, which implies that Balto-Slavic mobile ā-aorists were accented on the aorist marker at least in the 3rd singular: Bl.-Sl. *ar-ā̍.
Keywords: Baltic; Slavic; Balto-Slavic; preterit; aorist; accent; metatony; ablaut